Antibody Titre Study On Trivalent Foot And Mouth Disease Vaccine - Pankaj, Gautam Kumar; Kumar , Manoj; Gautam, Avnish Kumar; Bharti , Sanjay Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Present study was conducted on twenty cross bred cows based on evaluation of the antibody titre due to inoculation of oil adjuvant trivalent (O, A, Asia-1 vaccine strains) FMD vaccine employing Serum Naturalisation Test (SNT). The result showed a rise of SNT antibody titre at 30 days post vaccination (dpv) to protective level (2.01 log10 , 1.95 log10 , 1.75 log10 30 dpv in these serotypes O, A and Asia- 1 respectively) for all the three serotypes under study. The selected cows showed 72%, 88% and 72% protection for O, A and Asia- 1, respectively.
Keywords: FMD Vaccine; Oil Adjuvent; Serum Neutralisation Test; Cows